A novel mechanical test for the stress relaxation analysis of polymers. (February 2019) - de Melo, Caiuã Caldeira; Macêdo, Salvino; Sciuti, Vinicius Fiocco; Canto, Rodrigo Bresciani
Abstract: This paper describes a novel technique and methodology to characterize the stress relaxation behavior of polymers. The shaft-hole coupling test (SHCT) characterizes the stress relaxation mechanics of polymers through measurements of the decrease in the stress between a metallic shaft and a drilled polymeric specimen over time. The main benefits of SHCT are the low implementation costs and reduced time for which the mechanical testing machine is in continuous use, by adopting a device that can be detached from the machine. The stress relaxation of polytetrafluoroethylene (PTFE) was identified by the SHCT over the course of several days, verifying the feasibility of the technique. In order to describe the viscoelastic behavior of the material, an optimization routine via the finite element method (FEM) was used to calibrate the parameters of the Parallel Rheological Framework (PRF) model. Furthermore, the FEM analysis was able to reproduce the mechanical behavior of the material successfully and the methodology was validated via comparison with a conventional stress relaxation test under uniaxial compression loading. Highlights: A new method of assessing the stress-relaxation behavior of polymers is reported. The methodology allows the efficient use of laboratory equipment. FEM analysis is implemented to determine the constitutive model of the material. The validation of the methodology was done via a comparison with a conventional stress relaxation test. The methodology could be applied to other thermoplastic polymers and composites.